Experimental Analysis of Deformation Mechanics and Stability of a Shallow-Buried Large-Span Hard Rock Metro Station - Wei Li; Jiwen Bai; Kexian Li; Shijie Zhang (Advances in Civil Engineering)
Based on a certain Qingdao metro station, a large-scale three-dimensional model test has been carried out to investigate the stability of the surrounding rock masses (hard rock) and a large-span metro station under different excavation methods and technologies. The model test includes an entire section excavation, an arch-cover excavation, and a primary support arch-cover excavation. Compared with the entire section excavation, the primary support arch-cover method can effectively control the vault settlement and clearance convergence deformation of the surrounding rock masses, reducing them by 15–30%. The deformation itself goes through three stages: slow, abrupt, and stable. The excavation of the “middle hole” creates a drastic change in the tunnel vault during the arch-cover excavation; however, the timely application of supports can effectively constrain the range of disturbance caused by the excavation and weaken the degree of load agglomeration of the surrounding rock masses.